Ancient Egypt - McRae, Anne. (Florence, Italy : McRae Books, 2008)
An illustrated introduction to ancient Egypt, discussing the origins of the civilization, and providing information about its people, religion, war, art and architecture, and other aspects of daily life.
Includes index.
6.5
3-6
Keywords: Egypt -- Civilization -- To 332 B.C. -- Juvenile literature; Egypt -- Civilization; Egypt -- Civilization